Nimodipine vs. Milrinone – Equal or Complementary Use? A Retrospective Analysis - Jentzsch, Jennifer; Ziganshyna, Svitlana; Lindner, Dirk; Merkel, Helena; Mucha, Simone; Schob, Stefan; Quäschling, Ulf; Hoffmann, Karl-Titus; Werdehausen, Robert; Halama, Dirk; Gaber, Khaled; Richter, Cindy (Frontiers in Neurology, 2022)
Background Cerebral vasospasm (CVS) continues to account for high morbidity and mortality in patients surviving the initial aneurysmal subarachnoid hemorrhage (SAH). Nimodipine is the only drug known to reduce delayed cerebral ischemia (DCI), but it is believed not to affect large vessel CVS. Milrinone has emerged as a promising option. Our retrospective study focused on the effectiveness of the intra-arterial application of both drugs in monotherapy and combined therapy. Methods We searched for patients with aneurysmal SAH, angiographically confirmed CVS, and at least one intra-arterial pharmacological angioplasty. Ten defined vessel sections on angiograms were assessed before and after vasodilator infusion. The improvement in vessel diameters was compared to the frequency of DCI-related cerebral infarction before hospital discharge and functional outcome reported as the modified Rankin Scale (mRS) score after 6 months. Results Between 2014 and 2021, 132 intra-arterial interventions (144 vascular territories, 12 bilaterally) in 30 patients were analyzed for this study. The vasodilating effect of nimodipine was superior to milrinone in all intradural segments. There was no significant intergroup difference concerning outcome in mRS (p = 0.217). Only nimodipine or the combined approach could prevent DCI-related infarction (both 57.1%), not milrinone alone (87.5%). Both drugs induced a doubled vasopressor demand due to blood pressure decrease, but milrinone alone induced tachycardia. Conclusions The monotherapy with intra-arterial nimodipine was superior to milrinone. Nimodipine and milrinone may be used complementary in an escalation scheme with the administration of nimodipine first, complemented by milrinone in cases of severe CVS. Milrinone monotherapy is not recommended.